An integrated TTCN-3 test framework architecture for interconnected object-based internet applications. (1st January 2014) - Stepien, Bernard; Peyton, Liam; Shang, Ming; Vassiliou-Gioles, Theofanis
The internet is being transformed by rich interconnected object-based applications that support session-based interactions between users and applications over a variety of protocols (HTTP/s, SOAP, SIP). In this paper, we analyse and demonstrate the key benefits and advantages of TTCN-3, especially in terms of costs, as a test language and framework for testing internet applications. The integration of TTCN-3 and object-based unit test frameworks can provide superior testing of interconnected object-based internet applications but is currently limited by a small flaw in the TTCN-3 concrete layer architecture. We propose a refinement to the TTCN-3 standard which enables seamless integration with object-based unit test-frameworks. An existing TTCN-3 vendor has already incorporated the changes in the latest version of their tool and ETSI has established a committee to modify the TTCN-3 standard accordingly. We demonstrate the benefits with a series of examples involving both SIP and HTTP-based internet applications.